2012
DOI: 10.3945/jn.111.149070
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Plasma Proteins Modulate the Adaptive Immune Response in Mice with Acute Lung Inflammation

Abstract: We examined the effects of oral plasma protein supplements on the pulmonary adaptive immune response in mice challenged with intranasal LPS. C57BL/6 mice were fed a control diet or a diet supplemented with plasma proteins [spray-dried plasma (SDP) 80 g/kg] or with an Ig concentrate [(IC) 20 g/kg] from postnatal d 19 (weaning) until d 34. Mice were challenged with PBS or LPS from Escherichia coli at d 33 and killed 24 h later for leukocyte analyses or at d 34 and killed 6 h later for cytokine determination. LPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 35 publications
9
38
0
Order By: Relevance
“…In exploring a possible mechanistic pathway, we found that SDP treatment recovered the otherwise low Foxp3 expression found in SEB-challenged mice. Similar effects of plasma protein supplements were observed in the colitis mouse model [9] and in the acute lung inflammation model [8]. …”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In exploring a possible mechanistic pathway, we found that SDP treatment recovered the otherwise low Foxp3 expression found in SEB-challenged mice. Similar effects of plasma protein supplements were observed in the colitis mouse model [9] and in the acute lung inflammation model [8]. …”
Section: Discussionsupporting
confidence: 62%
“…There is intensive research underway to characterize nutritional strategies for the therapeutic management of inflammatory syndromes [4]. Dietary supplements prepared from functional proteins derived from foodstuffs [5], from bovine colostrum or milk [6], and from porcine or bovine animal plasma [7,8,9], have all been demonstrated to be effective in the amelioration and even prevention of inflammation in numerous experimental models. Recent evidence also indicates that functional protein supplements can be useful in the clinical management of patients with enteropathy (reviewed by [10]).…”
Section: Introductionmentioning
confidence: 99%
“…The appropriate dietary regimen to be administered during an anti-inflammatory metabolic treatment is also a relevant issue, since some forms of lipids are known to positively or negatively affect the inflammatory response (28,29). The effect of the inhibition of ITCH on adipose tissue might be additive to other pathways that have been demonstrated to be relevant to dampen metabolic inflammation in skeletal muscle, such as the TNF-a-converting enzyme pathway, which is positively restrained by pioglitazone, a PPAR-g agonist with anti-inflammatory effects, in patients with type 2 diabetes (30,31).…”
Section: Itchmentioning
confidence: 99%
“…Many studies have shown the immunomodulatory effects of oral Ig (porcine and ovine) in various rodent infection models (Balan, Han, Rutherfurd‐Markwick, Singh, & Moughan, ; Balan & Moughan, ; Maijó et al, , ; Pérez‐Bosque et al, , ). Pérez‐Bosque et al (, , ) determined the effects of an Ig concentrate in a rat intestinal inflammation model induced by the intraperitoneal administration of Staphylococcus aureus enterotoxin B (SEB).…”
Section: Biological Effects Of Igmentioning
confidence: 99%
“…Oral Ig supplement reversed the effects of SEB which increased the expression of TNFα and LTB4 in Peyer's patches and mucosa cytotoxic lymphocyte populations of T‐γδ cells and natural killer cells and the number of activated T lymphocytes in lamina propria. Maijó et al (Maijó et al, , ) examined the pulmonary innate and adaptive immune response in mice challenged with intranasal lipopolysaccharide (LPS).…”
Section: Biological Effects Of Igmentioning
confidence: 99%